Effects of dietary Hyssop, Hyssopus officinalis, extract on physiological and antioxidant responses of rainbow trout, Oncorhynchus mykiss, juveniles to thermal stress - Yousefi, Morteza; Hoseini, Seyyed Morteza; Kulikov, Evgeny Vladimirovich; Seleznev, Sergey Borisovich; Petrov, Aleksandr Konstantinovich; Babichev, Nikolay Valerievich; Kochneva, Margarita Vasilyevna; Davies, Simon John (Frontiers in Veterinary Science, 2022)
The present study aimed at assessing the effects of dietary Hyssop, Hyssopus officinalis, extract on rainbow trout, Oncorhynchus mykiss, responses to thermal stress. The juveniles (69.8 ± 0.38 g) were stocked in 12 through-flow tanks at a density of 12 fish per tank. Methanolic extract of Hyssop (HME) was added to diet at 0, 100, 250, and 500 mg/kg and the fish were fed (3% of biomass) over a 70-d period: 62 d at 13.3 ± 0.08°C and 7 d at 21–22°C. At the end of the trial, the plasma alanine aminotransferase (ALT), aspartate aminotransferase (AST), lactate dehydrogenase (LDH), triiodothyronine (T3), thyroxin (T4), cortisol, glucose, lactate, total antioxidant capacity (TAC), ascorbate, and the gill glutathione peroxidase (GPx), glutathione reductase (GR), glutathione-S-transferase (GST), and malondialdehyde (MDA). The results showed that HME had no significant effects on fish growth performance, survival, and feed efficiency. Dietary 250 mg/kg HME significantly decreased plasma ALT activity (P < 0.001), but showed no significant effects on plasma AST) (P = 0.106) activity, T3 (P = 0.992), and T4 (P = 0.070) levels. Thermal stress significantly (P < 0.001) increased plasma ALT and AST activities, but lowered plasma T3 and T4 levels. Dietary HME and thermal stress had interaction effects on plasma cortisol (P < 0.001), glucose (P = 0.007), lactate (P = 0.010), LDH (P = 0.005), TAC (P = 0.038), ascorbate (P < 0.001), and the gill GPx (P = 0.001), GR (P < 0.001), GST (P < 0.001), and MDA (P = 0.001). Thermal stress significantly increased plasma cortisol, glucose, lactate, and LDH, the gill GPX, GR, and GST, but dietary HME supplementation significantly reduced such elevations, particularly at 250 mg/kg level. Dietary HME significantly increased plasma TAC before the thermal stress and mitigated the stress-induced decreased in TAC, particularly at 250 mg/kg level. Dietary HME significantly decreased the gill MDA before and after the thermal stress, and lowest MDA was observed in 250 mg/kg HME level. Based on the present results, 250 mg/kg HME is recommended as suitable dose to improve antioxidative responses and hepatoprotection in rainbow trout under heat stress.